Pharmaceutical Distribution Market Channels in Poland - Agnieszka Woś (Contemporary Economics)
Distribution on the pharmaceutical market in Poland is interesting and the most difficult sphere to manage. Numerous varied and specialized companies operating on the market cause that the processes of choosing middlemen in distribution channels are very complex. The hereby article presents the role and location of the companies operating within distribution channels on the pharmaceutical market. It draws attention to the development of non-pharmacy and non-wholesale sales channels.